AKTIVITAS FISIK LANSIA HIPERTENSI PADA MASA PANDEMI COVID 19 - Kartiningrum, Eka Diah; Ikrimah, Umi Habibatul; Suhartanti, Ika (MEDICA MAJAPAHIT, 2022)
Hypertension is a degenerative disease that often occurs in the elderly, but one of the most dominant factors influencing the occurrence of hypertension in the elderly is physical activity. The purpose of this study was to determine physical activity in elderly hypertensives during the Covid-19 Pandemic at the Elderly Posyandu, Gayaman Village, Mojokerto Regency. This type of research is quantitative research using observational methods with a cross sectional approach. The population in this study were all hypertensive elderly who were recorded at the elderly Posyandu in Gayaman Village, Mojokerto Regency, as many as 65 hypertensive elderly, the sample used was 37 people who were selected using Simpe Random Sampling. Data was collected using a questionnaire through observation and interviews, then the data was analyzed using the Spearman Rank Correlation test. The results showed that most of the respondents had high physical activity as many as 26 respondents (70.3%). The heavier the physical activity, the normal the blood pressure. Lack of physical activity can increase blood pressure. Therefore it is hoped that the Gayaman Village Elderly Posyandu will carry out health promotion efforts to prevent hypertension which can be carried out independently by health cadres.